Specific antibody and immunoglobulin responses after intestinal colonization of germ-free piglets with non-pathogenic Escherichia coli O86 - Cukrowska, Bożena M; Kozáková, Hana; Řeháková, Zuzana; Šinkora, Jiří; Tlaskalová, Helena (Urban & Fischer, 2001)
The study focuses on immune, mucosal and cell responses after intestinal colonization with Escherichia coli O86 in pigs.
Keywords: imunita; experimentální medicína; Germ-Free Life; Escherichia coli; střevní sliznice; Antibodies; modely u zvířat; alergologie a imunologie; B-Lymphocytes; imunoglobuliny; Swine; prasata; gnotobiologické modely; Models, Animal; B-lymfocyty; Immunity; protilátky; Intestinal Mucosa; Immunoglobulins